Influence of Product Quality, Service Quality, and Price on Purchase Decision at Lesehan Jembol Restaurant in Palopo City - Sakinah*, Andi Waru Virgincia; Gita, Gita; Handini, Handini; Mahmut, Cici; Supri, Baharman (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Product quality, service quality, and price are key factors that significantly influence customer purchase decisions. This study aims to examine the impact of product quality, service quality, and price on purchasing decisions at Lesehan Jembol Restaurant in Palopo City, including an in-depth analysis of how each factor, specifically product quality and service quality, affects these decisions. The research employs several data collection techniques, including interviews, questionnaires, and observations. The types of data collected include qualitative data (in the form of words) and quantitative data (in the form of numbers). Primary data is obtained directly through interviews with respondents, while secondary data is sourced from books, documents, the internet, and print media. Data analysis is conducted using descriptive methods, validity tests, and reliability tests of the questionnaire with the aid of statistical tools. The findings indicate that product quality, service quality, and price significantly affect purchase decisions at Lesehan Jembol Restaurant in Palopo City, thereby confirming the first hypothesis. Specifically, product quality has a significant impact on purchase decisions, supporting the second hypothesis. Service quality also significantly influences purchase decisions, thus confirming the third hypothesis. Additionally, price has a significant effect on purchase decisions, supporting the fourth hypothesis.